Evolution of the diagnostic criteria of antibody-mediated rejection of renal allografts: Banff classification updates - Mubarak,Muhammed (2013)
Alloimmune rejection is one of the most common causes of both acute and chronic renal allograft dysfunction throughout the world. It is also one of the most important causes of graft loss, both in the short - and the long-term. The process of rejection of the allograft tissue is mediated predominantly by the acquired or specific alloimmune mechanisms of both humoral and T cell-mediated arms. More recently, evidence is also accumulating which supports the role of innate immunity in initiating this process. The diagnosis of the rejection process may be suspected on clinical grounds, with some support from the laboratory investigations and imaging studies, but the gold standard test for an accurate diagnosis and specifically its categorization is still the invasive procedure of renal allograft biopsy. In addition, numerous molecular markers in the serum and urine have also been investigated as non -invasive alternatives to renal allograft biopsy for the diagnosis of acute rejection, but the renal allograft biopsy provides additional valuable information over and above just the diagnosis of rejection. During early 1990s efforts began to standardize the histopathological study of renal allograft biopsies for the uniform reporting of the pathological lesions. These efforts have continued with a missionary zeal and have resulted in marked refinements in the diagnostic criteria and categories of rejection seen on allograft biopsies. The presente series attempts to address the evolutionary changes in the diagnostic criteria and the classification of the rejection process on renal allograft biopsies as these took place over the years since early 1990s. In this review, we will discuss the changes that have occurred in the diagnosis and categorization of antibody mediated rejection and the focus will be on the morphological basis of their diagnosis and categorization